Predictive value of platelet-to-albumin ratio for acute kidney injury in patients with decompensated cirrhosis: A double-center study - Nghia, Nguyen Nhu; Bao, Nguyen The (Tạp chí Nghiên cứu Y học, 2024)
This study aims to evaluate the value of the platelet-to-albumin ratio (PAR) in predicting acute kidney injury (AKI) in patients with decompensated cirrhosis. A descriptive cross-sectional analysis was conducted at multiple centers on 295 patients with decompensated cirrhosis, treated at the Department of Gastroenterology - Can Tho Central General Hospital and the Department of Gastroenterology - Bac Lieu General Hospital from June 2019 to May 2021. The results showed that the average age of the study subjects was 60.0 ± 12.5 years old, with a male/female ratio of 3/2. The average albumin level was relatively low, at 27.18 ± 6.29 g/L. The median platelet count was 73 x 109/L. The median platelet-to-albumin ratio was 2.99. The incidence of acute kidney injury in patients with decompensated cirrhosis was 33.9%. At a cut-off point of the serum platelet-to-albumin ratio ≥ 3.64, the predictive value for the incidence of acute kidney injury in patients with decompensated cirrhosis was recorded with an area under the ROC curve (AUC) of 96.7% (95%CI: 95% - 98%).